Если \(a - 2b = 15\)а также \(ab = 11\)затем найдите значение \(a^2 + 4b^2\)?

0
0

Если \(a — 2b = 15\)а также \(ab = 11\)затем найдите значение \(a^2 + 4b^2\)?

0
0

\[a^2+4b^2=269\] Объяснение: \[(a-2b)^2=a^2-4ab+4b^2= 15^2\] тогда \[a^2+4b^2=15^2+4 ab = 15^2+4 xx 11 =269\]

0
0

\[a^2+4b^2=269.\] Объяснение:

Способ I
Учитывая это, \[a-2b=15\] \[:. (a-2b)^2=15^2=225.\] \[:. a^2-2*a*2b+4b^2=225,\] т.е. \[a^2-4ab+4b^2=225.\] Позволить, \[ab=11\] в этом мы имеем, \[a^2-4(11)+4b^2=225.\] Следовательно, \[a^2+4b^2=225+44=269.\] Способ II
Заметь \[(a+2b)^2+(a-2b)^2=2(a^2+4b^2).\] Здесь мы заменим \[(a+2b)^2\] по \[(a-2b)^2+8ab,\] получить, \[(a-2b)^2+8ab+(a-2b)^2=2(a^2+4b^2),.\] и теперь положить заданные значения, \[225+8*11+225=2(a^2+4b^2)=538,\] так, \[(a^2+4b^2)=538/2=269,\] как прежде!

Показано 2 результатов